2007
DOI: 10.1177/0265659007080684
|View full text |Cite
|
Sign up to set email alerts
|

Using an observational framework to investigate adult language input to young children in a naturalistic environment

Abstract: The correlation between the communicative intent of parents, in terms of their expectation of a response and the response patterns of young children aged 23-25 months during parent-child interactions was investigated. An Observational Framework was used to code these parameters in interactions between 36 children and their mothers. The children were assigned by cluster analysis to 'advanced', 'typical' and 'delayed' language groups and their responses were coded with respect to the degree of correctness or app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In all the research into the role that input plays in child language development, the most attention has been paid to mothers. However, a growing literature explores the role of fathers [23][24][25] (including the work by Guest Editor Rowe and her colleagues in this issue), teachers, 27,29 day care providers, 54 SLPs, 26 and even nannies. 55 In general, findings are congruent with those found in examining the role of maternal input to children, with a few notable exceptions.…”
Section: How Input Affects Children's Language Learningmentioning
confidence: 99%
“…In all the research into the role that input plays in child language development, the most attention has been paid to mothers. However, a growing literature explores the role of fathers [23][24][25] (including the work by Guest Editor Rowe and her colleagues in this issue), teachers, 27,29 day care providers, 54 SLPs, 26 and even nannies. 55 In general, findings are congruent with those found in examining the role of maternal input to children, with a few notable exceptions.…”
Section: How Input Affects Children's Language Learningmentioning
confidence: 99%
“… Parental responsiveness. Responsiveness is the rate at which carers respond to a child's gestures, vocalisations or other communicative acts (Anderson and Marinac 2007). Yoder and Warren (2001) report that the parents of children with language impairments are less responsive to the child's non‐verbal communication but focus heavily on their spoken language.…”
Section: Introductionmentioning
confidence: 99%
“…Anderson and Marinac (2007) took a different approach to studying the relationship between maternal speech and child language development. Anderson and Marinac (2007) investigated…”
Section: Maintaining and Extending Child's Interestmentioning
confidence: 99%
“…In addition to maternal factors that contribute to parent-child interactions that effect language development in children, there may also be child behaviors which facilitate or inhibit interactions that effect child language development. One study demonstrated a relationship between infant's high levels of attention and their subsequently high vocal responsiveness (Gartstein, Crawford, & Robertson, 2008 Anderson and Marinac (2007) looked at children's follow through or response in interactions with their parents and the effect these had on language development. Children were classified as having delayed speech, typically developing speech, or advanced speech.…”
Section: Child Engagementmentioning
confidence: 99%
See 1 more Smart Citation